Lobbying in Europe : public affairs and the lobbying industry in 28 EU countries - Bitonti, Alberto ; Harris, Phil (Palgrave Macmillan, 2020)
This book provides a clear, systematic and up-to-date picture of the vast and dynamic industry of lobbying and Public Affairs in Europe, not only at EU level, but specifically in each of the 28 EU Member States. Using contributions from political scientists and lobbyists from each country, the volume offers a comprehensive review of the European lobbying industry, tackling elements such as the institutional framework and the political culture of each country, the perception of lobbyists by public opinion and politicians, the professionalization and the numbers of the industry in each country, the regulation of the sector (through dedicated laws, self-imposed ethical codes, etc.). This is a benchmark publication for all those studying or working in the field of Lobbying, Public Affairs, Communication and Business and Politics in or with EU countries.Chapter 1.1. An Introduction to Lobbying in Europe; Alberto Bitonti and Phil Harris.- Chapter 1.2. The role of lobbying in modern democracy: a theoretical framework; Alberto Bitonti.- Chapter 2.0. Lobbying in EU; Simon Levitt, Simon Bryceson and Frederick van Mierlo.- Chapter 2.1. Lobbying in Austria; Peter Köppl.- Chapter 2.2. Lobbying in Belgium; Tine Destrooper.- Chapter 2.3. Lobbying in Bulgaria; Detelina Dineva.- Chapter 2.4. Lobbying in Croatia; Natko Vlahovic and Dubravka Sinčić Ćorić.- Chapter 2.5. Lobbying in Cyprus; Maria Kepardis and Christina Neophytidou.- Chapter 2.6. Lobbying in Czech Republic; Štěpán Soukeník, Miloš Gregor and Anna Matušková.- Chapter 2.7. Lobbying in Denmark; Peter Andreas Münster and Andreas Hjørnholm.- Chapter 2.8. Lobbying in Estonia; Andreas Kaju and Ott Lumi.- Chapter 2.9. Lobbying in Finland; Kimmo Collander, Eero Rämö and Urho Blom.- Chapter 2.10. Lobbying in France; Didier Sallé and Francesco Marchi.- Chapter 2.11. Contents: Lobbying in Germany; Dominik Meier.- Chapter 2.12. Lobbying in Greece; George Limperis.- Chapter 2.13. Lobbying in Hungary; József Péter Martin and Miklós Ligeti.- Chapter 2.14. Lobbying in Ireland; Gary Murphy.- Chapter 2.15. Lobbying in Italy; Pier Luigi Petrillo.- Chapter 2.16. Lobbying in Latvia; Valts Kalnins.- Chapter 2.17. Lobbying in Lithuania; Saulius Spurga.- Chapter 2.18. Lobbying in Luxembourg; Paul-Michael Schonenberg.- Chapter 2.19. Lobbying in Malta; Mark Harwood.- Chapter 2.20. Lobbying in Netherlands; Peter Van Keulen.- Chapter 2.21. Lobbying in Poland; Witold Michalek.- Chapter 2.22. Lobbying in Portugal; Joaquim Martins Lampreia.- Chapter 2.23. Lobbying in Romania; Laura Florea and Bogdan Dima.- Chapter 2.24. Lobbying in Slovakia; Patrik Zoltvany.- Chapter 2.25. Lobbying in Slovenia; Danica Fink Hafner.- Chapter 2.26. Lobbying in Spain; Maria Rosa Rotondo and Rafael Rubio Núñez.- Chapter 2.27. Lobbying in Sweden; Anna-Karin Hedlund.- Chapter 2.28. Contents: Lobbying in United Kingdom; Conor McGrath.- Chapter 3.1. Lobbying and Public Affairs in Europe: a comparative overview; Alberto Bitonti, Phil Harris, Claudia Mariotti.